Anisotropic atom motion on a row-wise antiferromagnetic surface - Felix Zahner; Soumyajyoti Haldar; Roland Wiesendanger; Stefan Heinze; Kirsten von Bergmann; André Kubetzka (Nature Communications)
Abstract Diffusion on surfaces is a fundamental process in surface science, governing nanostructure and film growth, as well as molecular self-assembly, chemical reactions and catalysis. Atom motion on non-magnetic surfaces has been studied extensively both theoretically and by real-space techniques such as field ion microscopy and scanning tunneling microscopy. For magnetic surfaces ab-initio calculations have predicted strong effects of the magnetic state onto adatom diffusion, but to date no corresponding experimental data exists. Here, we investigate different atoms on the hexagonal Mn monolayer on Re(0001) using scanning tunneling microscopy at T = 4.2 K and density functional theory. Experimentally, we observe one-dimensional motion of Co, Rh, and Ir atoms on the hexagonal Mn layer, dictated by the row-wise antiferromagnetic state. Co atoms move up to 10 nm when their motion is initiated by local voltage pulses. Our calculations reveal anisotropic potential landscapes, which favor one-dimensional motion for both Rh and Co atoms, avoiding induced Rh spin moments and conserving the Co spin direction during movement, respectively. These findings demonstrate that the magnetic properties of a system can be a means to control adatom mobility, even in the case of non-magnetic adatoms.